2013
DOI: 10.1155/2013/471346
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-Dependent High-Affinity Potent Ricin-Neutralizing Monoclonal Antibodies

Abstract: Ricin is a potential biothreat agent with no approved antidote available for ricin poisoning. The aim of this study was to develop potent antibody-based antiricin antidotes. Four strong ricin resistant hybridoma clones secreting antiricin monoclonal antibodies (mAbs) were developed. All four mAbs are bound to conformational epitopes of ricin toxin B (RTB) with high affinity (K D values from 2.55 to 36.27 nM). RTB not only triggers cellular uptake of ricin, but also facilitates transport of the ricin toxin A (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…There are a large number of RT-specific MAbs from mice and NHPs described in the literature that have been shown to be able to passively protect mice against RT challenge [34][35][36][37][38][39][40][41][42]. It is unclear whether the PB10/SylH3 cocktail is any more potent that other possible combinations of MAbs described, since systematic comparisons have not been conducted, although certainly the two MAbs are the best within our collection [10].…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of RT-specific MAbs from mice and NHPs described in the literature that have been shown to be able to passively protect mice against RT challenge [34][35][36][37][38][39][40][41][42]. It is unclear whether the PB10/SylH3 cocktail is any more potent that other possible combinations of MAbs described, since systematic comparisons have not been conducted, although certainly the two MAbs are the best within our collection [10].…”
Section: Discussionmentioning
confidence: 99%
“…If the antibody binds to the pathogen or toxin at the right location, the antibody will efficiently block the entry of pathogen or toxin into cells; otherwise, the blockage will only be partial or null. For example, a recently developed anti-ricin mAb showed extremely high efficacy since it binds to the part of ricin which is responsible for binding to the cell surface to initiate ricin entry into cells [45]. Only a small amount of antibody (0.25 mg/kg) was required for complete protection against lethal ricin challenge [26,[45][46][47].…”
Section: Antibody Efficacymentioning
confidence: 99%
“…The RTB subunit of ricin contains two galactose binding sites that function independently and are distant from one another [ 34 , 73 ]. Hu et al generated four MAbs directed against the RTB subunit and found that all of them bound to conformational epitopes with a high affinity.…”
Section: Synergistic Neutralization Of Mab Cocktailsmentioning
confidence: 99%